THE EFFECT OF THE AMOUNT OF MAIN AMINO ACIDS SYNTHESIZED IN THE RESERVOIR OF THE SILKWORM’S SILK GLAND ON THE TECHNOLOGICAL PROPERTIES OF SILK FIBER - Chorshanbi Bekkamov; Raxmanova X. E.; Abdullayev A. N.; Boxodirova U. A.; Sadullaeva G. S. (Bright Mind Publishing, 2025)
This study focuses on one of the crucial physiological and biochemical processes in the silkworm's body—silk production. The research examines the developmental stages and biological characteristics of the silk-producing gland. The experiment was conducted in the “Biology and Embryology of the Silkworm” laboratory at Tashkent State Agrarian University, analyzing the development of silkworms at their fifth instar. The obtained results indicate that the weight and volume of the silk gland increase progressively as the larva grows. Notably, the study analyzed the quantitative indicators of essential amino acids in the silk gland during silk production, revealing a significant increase during the fifth instar. The findings of this research can contribute to improving the quality of cocoons and producing silk fibers with high technological properties.
Keywords: Silkworm, breed, hybrid, nutritious mulberry leaf, body characteristics, silk gland weight, volume, fifth-instar larvae, silk-producing gland, silk gland activity, liquid reservoir, Lyonet's gland, pressing apparatus, silk fluid, fibroin, sericin, silk fiber, chemical elements, amino acids, quantity, fiber length, winding, metric number.